Distribution and abundance of squat lobster (Pleuroncodes monodon) and its association with anchoveta in the coastal zone of the Peruvian Current (1998–2024) - Castillo, Pedro Ramiro; La Cruz, Luis; Valdez, Carlos; Cuadros, Gustavo; Ferrel, Ketty; Pozada-Herrera, Marissela; Cornejo, Rodolfo; Aliaga, Aníbal; Grados, Daniel (Frontiers in Marine Science, 2025)
The squat lobster or munida (Pleuroncodes monodon) is one of the most abundant species in the coastal zone of the Peruvian Current. Due to its high incidence of occurrence and biomass, it has been monitored since 1998 by the Instituto del Mar del Perú (IMARPE) through the Hydroacoustic Assessment Surveys for Anchoveta and Other Pelagic Resources. In this study, 59 surveys conducted between 1998 and 2024 were analyzed to study the spatial distribution, abundance, and ecological relationship of munida with anchoveta (Engraulis ringens). The results showed that between 1998 and 2000, munida expanded its distribution northward along the Peruvian coast, while from 2001 onward its range remained relatively stable. A clear seasonal pattern was identified: during winter and spring, both the distribution area and inertia increased, and the species tended to occur farther from the coast, whereas in summer and autumn the distribution contracted, except during anomalous oceanographic events (e.g., warm or cold conditions). Vertically, munida generally inhabited the surface layer down to approximately 168 m, although during the 2015 -2016 El Niño event it was recorded as deep as 203 m. The average biomass throughout the study period was close to 2.04 million tons, with a maximum of 5.38 million tons recorded during survey 1703-04. Munida was also the species most closely associated with anchoveta, and when both occurred together, their interaction varied depending on the time of day, probably reflecting diel vertical migration and differential aggregation behaviors. These findings suggest that munida is a key component of the Peruvian Current ecosystem, whose variability is influenced both by seasonal cycles and by anomalous oceanographic conditions, and that its association with anchoveta may have implications for ecosystem functioning and fisheries management in the region.